PERAN ISTRI DALAM PEREKONOMIAN KELUARGA DIDESA PARIT BARU KECAMATAN TAMBANG KABUPATEN KAMPAR - Rina Susan; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Farmer is a person or a community residents who have a livelihood as farmers to meet their needs and the needs of his family. Farm workers are those who work the fields in the land or property of others for a wage from the owner of the land. The problem in this research is a farm laborer's wife 1. How to play its role in the family? 2. How does the wife's involvement in the farm workers help the family economy? The purpose of this study was to determine the wife of farm workers to play its role in the family and to know his wife's involvement in the family economy. Population and sample in this study was the wife of farm workers, data collection techniques with observation and interviews, data analysis techniques using quantitative descriptive. Research results generally show that the wife doing homework is done before leaving for work and farm laborers working wife to help him meet the needs of family life driven by economic factors, family and children's education and to increase family income. Most of the education level of respondents was limited to SD, then the wife to work the informal sector does not need special training or higher education, but it only took power. Income of the respondent husband average between Rp 1000000-2000000 each month, and his wife earned income each month mostly around Rp 600,000 per month. The wife is not only in charge of taking care of his family but also to work for a living wife to help her husband in meeting the needs of the family.Keywords: Role, family economy